2017
DOI: 10.14474/ptrs.2017.6.2.59
|View full text |Cite
|
Sign up to set email alerts
|

The effect of single trial transcutaneous electrical nerve stimulation on balance and gait function in elderly people with dementia: a pilot study

Abstract: Objective: Elderly people with dementia experience not only cognitive dysfunction but also motor function deficits, such as balance and gait impairments. Recently, transcutaneous electrical nerve stimulation (TENS) has been used to reduce pain as well as to control muscle spasm, spasticity and motor performance in various types of subjects. The purpose of this study determined the effect of a single trial TENS on balance and gait function in elderly people with dementia. Design: A randomized controlled trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…The TENS group had a higher navicular height and a lower fear of falling than the CON group. The clinical relevance of using TENS is that TENS impulse is speculated to enhance the strength of the plantar foot intrinsic muscles, as supported by [27]. A study investigated the strengthening effect of using TENS and found an increase in the strength of the plantar foot flexor muscles in elderly individuals.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The TENS group had a higher navicular height and a lower fear of falling than the CON group. The clinical relevance of using TENS is that TENS impulse is speculated to enhance the strength of the plantar foot intrinsic muscles, as supported by [27]. A study investigated the strengthening effect of using TENS and found an increase in the strength of the plantar foot flexor muscles in elderly individuals.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, another study revealed an increase in muscle mass by 6.6% following electrical muscle stimulation application, which was investigated using dual-energy X-ray absorptiometry [29]. The explanation of this change can be due to the neural adaptations stimulated by the generating of direct impulse to nerves inside the targeted muscle, subsequently leading to twitch contractions [27]. Moreover, electrical impulses likely reverse the physiological recruitment pattern of motor units where fast twitches become faster than slow units.…”
Section: Discussionmentioning
confidence: 99%
“…We use published clinic trial data [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] and our previous published models of brain memories [19,20], meridian channels [21,22] as well as theories of biochemistry, learning [23,24] and artificial neural network (ANN) [25,26].…”
Section: Methodsmentioning
confidence: 99%
“…However, the responses in the related working memories are distributed too. Therefore, our model in this figure gives an explain the clinical researches [14,15]: the distributed stimulation improves the patient's recalling abilities, but may disturb normal people's retrieving memories.…”
Section: Auditory or Visual Cortices Entorhinal Cortexmentioning
confidence: 99%
See 1 more Smart Citation